Empowering community vitality: synergistic renovation strategies for abandoned boiler houses in urban renewal contexts - Lei Chen; Mengru Li; Tange Liang; Mingwan Shen (Journal of Asian Architecture and Building Engineering)
There are numerous abandoned boiler houses located in old communities in China’s severely cold regions. During the urban renewal process, the current renovation of boiler houses is often carried out in isolation, neglecting the unique sociospatial context of old communities. This fragmented way has resulted in suboptimal outcomes and a lack of community vitality. Moreover, research has determined that aging communities and boiler houses form an inseparable whole, sharing common characteristics in terms of era, location, and type. Based on the regional architectural theory, this paper employs a holistic approach to propose renovation strategies for community boiler houses: On one hand, decision-makers should adopt “overall layout control” to expand the perspective, establish an overall layout, break down boundaries, integrate functions, highlight the core, and establish order; On the other hand, through “core reinforcement and association” and “community structural layout” design to activate community vitality.